"I don't mean to sound racist but … " Transforming racism in transnational Europe. Issue 5 (9th April 2018) - Nowicka, Magdalena
ABSTRACT: Thinking of racism through the lens of its geographies and temporality – a transnational lens, as I understand it – is productive for our understanding of the current process of social integration of immigrants in European cities. I argue that an interactive model of racism can help us understand the spread (and revival) of racism in Europe, and develop a new take on intersections of racism and immigration. Using the example of the Polish "post-enlargement" immigration to England, I scrutinize how racism is altered through social networks spanning localities within and across national borders. I demonstrate how the research participants incorporate, reproduce, and transform racism present in the British multicultural public space into a cultural repertoire (habitus) they internalized before migration. I argue that racism is a transnational outcome of ongoing negotiations between past and current experiences, and between parties in two or more geographical locations.